Construction of Leadership Values through Digital Family Communication: A Study of Santri in Islamic Pesantren: - Machyudin Agung Harahap; Susri Adeni (Institut Agama Islam Negeri (IAIN) Curup, 2026)
Purpose − Pesantren are currently facing the dynamics and dilemmas of the development of digital communication technology, which can have various negative impacts on santri. On the other hand, the presence of digital communication technology can also facilitate santri in maintaining communication with their families. Subsequently, a series of rules emerges regarding the use of digital communication technology. This then creates patterns of digital communication and leadership values between santri and their families. The study aims to analyze leadership values through family digital communication among santri. Method − This research employs a fenomenology qualitative approach through structured interviews with eight male santri using a purposive sampling technique. The study also utilizes NVivo 15 and Microsoft Visio 365 to obtain themes, data descriptions, data visualization, and to draw conclusions. Findings − The results show that there are variations in digital communication patterns between santri and their families, such as protective, pluralistic, and laissez-faire. Family digital communication also provides leadership values to santri, including responsibility, cooperation, mutual respect, honesty, optimism, self-confidence, patience, and critical thinking. Furthermore, the leadership values provided develop into practices that are actualized through actions to verify truth and coordination. In this regard, pesantren play a role as mediators that regulate and shape digital communication between santri and their families through ethical rules and limitations on the use of technology.